Interactive Effects of LED Spectrum and Nitrogen Levels on Physiological Changes and Yield of Strawberry (Fragaria × ananassa Duch.) - Sirajo Salisu Jibia; Kanokwan Panjama; Chaiartid Inkham; Takashi Sato; Norikuni Ohtake; Soraya Ruamrungsri (Plants)
Strawberries are valued globally for their nutritional, aesthetic, and economic benefits. Optimizing blue-to-red LED ratios and nitrogen levels is essential for sustainable indoor strawberry cultivation. This factorial study investigated the effects of blue and red LED combination ratios (L1; 1:3, L2; 1:4, and L3; 1:6) and nitrogen levels (N1; 100 and N2; 200 mg/L) on the physiology and performance of strawberries in a plant factory. The results revealed that the interaction of L3 coupled with N2 maximized the vegetative growth of strawberry plants, whereas L2 and N2 produced the greatest biomass, while L2 interacted with N1 to expedite flowering. Photosynthesis and transpiration were enhanced by L3, particularly with 100 mg/L of nitrogen. The highest fruit yield and total soluble solids were obtained at the interaction of L3 and N1. Leaf nutrient analysis showed the highest nitrogen concentration at L1, while potassium increased with higher red LED ratios. The 100 mg/L nitrogen treatment resulted in higher leaf potassium concentrations than the 200 mg/L. These findings emphasize that LED spectra and nitrogen levels interact to optimize the physiology, vegetative and reproductive growth, maximizing fruit yield and quality in indoor strawberry cultivation. The study also concludes that the application of blue and red LED in the ratio of 1:6 with 100 mg/L nitrogen can improve indoor ‘Praratchatan 80’ strawberry performance.